2009
DOI: 10.1007/s00280-009-1069-7
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and oxaliplatin in patients with unresectable biliary cancer including gall bladder cancer: a Korean Cancer Study Group phase II trial

Abstract: The GEMOX regimen demonstrated a modest antitumor activity and is well tolerated in patients with advanced BTCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 15 publications
5
50
0
Order By: Relevance
“…Although the combination of these drugs improves the progression-free and overall survival compared with gemcitabine alone, the median overall survival is still modestly approaching 1 year in metastatic CCA 244 . If cisplatin is contraindicated (for example, in renal insufficiency), safety and efficacy using gemcitabine in combination with oxaliplatin have been demonstrated in several phase II studies 248,249 . When gemcitabine and cisplatin fail, no established standard regimens in the second-line setting are available 250 .…”
Section: Chemotherapymentioning
confidence: 99%
“…Although the combination of these drugs improves the progression-free and overall survival compared with gemcitabine alone, the median overall survival is still modestly approaching 1 year in metastatic CCA 244 . If cisplatin is contraindicated (for example, in renal insufficiency), safety and efficacy using gemcitabine in combination with oxaliplatin have been demonstrated in several phase II studies 248,249 . When gemcitabine and cisplatin fail, no established standard regimens in the second-line setting are available 250 .…”
Section: Chemotherapymentioning
confidence: 99%
“…Based on these results, the combination of gemcitabine and cisplatin is considered to be the standard of care for first-line chemotherapy for patients with advanced or metastatic biliary tract cancers. Examples of other gemcitabine-based or fluoropyrimidine-based (fluorouracil or capecitabine) regimens with demonstrated activity in phase II trials include gemcitabine and cisplatin or oxaliplatin [165][166][167][168][169][170][171][172][173] ; gemcitabine and fluoropyrimidine [174][175][176][177][178][179] ; and fluoropyrimidine and oxaliplatin or cisplatin. [180][181][182][183] Triple-drug chemotherapy regimens also have been shown to be effective in patients with advanced biliary tract cancers, albeit in a very small number of patients.…”
Section: Chemotherapy and Chemoradiation For Advanced Biliary Tract Cmentioning
confidence: 99%
“…Further number of phase II studies suggested that oxaliplatin added to gemcitabine (GEMOX) may have comparable historical outcomes than cisplatin with a range of reported OS of 8.3 to 11 months (25)(26)(27)(28)(29). A recent randomized phase II trial suggested that GEMOX may be superior to 5-FU or best supportive care (BSC) alone (OS 9.5 vs. 4.5 vs. 4.6 months respectively, P=0.032) (30).…”
Section: Therapy Options For Unresectable Diseasementioning
confidence: 99%